The unmet needs of PCPNDT act in the women of the general population in North India - Tandon, Neha Pruthi; Bachani, Sumitra; Kaura, Shreya; Dewan, Rupali; Arora, Renu (International Journal Of Community Medicine And Public Health, 2020)
Background: Government of India has taken measures to stabilize the sex ratio by introducing Pre-Conception and Pre-natal diagnostic techniques act (PCPNDT). Despite various amendments, awareness about the act amongst women appears suboptimal. Present study was aimed to assess the knowledge and attitude regarding PCPNDT act in women attending tertiary care hospital and to determine the lacunae regarding its implementation. Methods: Cross-sectional study was conducted by Department of Obstetrics and Gynecology. Total of 1000 women were included and a pre-designed questionnaire was used to get information regarding socio-demographic details and to assess the knowledge and attitude towards the PCPNDT Act. Data was analyzed using Statistical package of social sciences (SPSS) 16.0. Results: In the present study, 75% women were in the age group 21-40 years and were Hindus. Only 25% (n=256) knew about PC-PNDT act. Majority of the subjects (n=880, 88%) had no knowledge that the doctors are also punishable. Attitude of women was also not a benchmark as 40 % women were keen to know the sex of their unborn child and 66% of the participants said that having a male was important for the family. Conclusions: The knowledge about PC‑PNDT act was below the expected standards. The attitude of women towards sex determination of unborn child and sociocultural influences favoring male child are still deeply rooted in society. Active involvement of media, social workers and health staff for dissemination of information to the public and to bring change in attitude of women is the need of the hour.